Repair of anomalous coronary artery from the pulmonary artery: A-signal center 20-year experience. (15th November 2016) - Qiu, Jiawei; Li, Shoujun; Yan, Jun; Wang, Qiang; Song, Yunhu; Sun, Hansong; Li, Dianyuan
Abstract: Background: Anomalous origin of coronary artery from the pulmonary artery (ACAPA) is a rare congenital coronary malformation with a high mortality whether in infants or adult patients. This study reviews 20 years of surgical treatment in a single center and aims to establish the optimal surgical strategies for this rare pathology. Methods and results: From April 1994 to March 2015, 96 consecutive patients aged from 3 months to 60 years underwent coronary repair surgery. The surgical procedures included ligation (3 cases), ligation along with CABG (6 cases), transpulmonary baffling (Takeuchi Procedure, 14 cases) and directly implantation of the anomalous coronary artery (ACA) into the aorta (73 cases). Postoperative extracorporeal mechanical circulatory support (ECMO) was necessary in 4 cases. Mitral valve repair was performed in 40 patients with moderate or severe mitral regurgitation (MR). Mitral replacement was performed in one patient with severe MR. There were one early and two late deaths. One patient underwent a second operation because Baffle leaks. During mean 10.45 ± 8.96 year follow-up (1 month–18 years), both early and late improvement of left ventricular function was observed in most patients (8 patients lost of follow-up). Conclusions: The establishment of a two-coronary system is the main goal of surgical therapy today. In different procedures, the direct implantation of the ACA into the ascending aorta is the best method and has good long-term results. ECMO as a bridge to recovery that will play an integral part in moderns' surgical treatment.